2000
DOI: 10.1007/s004640000186
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted vs open ileocolic resection for Crohn’s disease

Abstract: Compared to open surgery, laparoscopic ileocolic resection for Crohn's disease is associated with similar morbidity rates, a shorter hospital stay, and improved cosmetic results, justifying the laparoscopic approach as the procedure of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 17 publications
7
118
2
3
Order By: Relevance
“…Patients undergoing restorative proctocolectomy may benefit from a laparoscopic approach, as demonstrated by previous studies comparing laparoscopic procedures with open surgery for inflammatory bowel disease [1][2][3][4]. Whereas these studies reported on resections confined to only small parts of the bowel, proctocolectomy belongs to the most extensive gastrointestinal resections.…”
mentioning
confidence: 99%
“…Patients undergoing restorative proctocolectomy may benefit from a laparoscopic approach, as demonstrated by previous studies comparing laparoscopic procedures with open surgery for inflammatory bowel disease [1][2][3][4]. Whereas these studies reported on resections confined to only small parts of the bowel, proctocolectomy belongs to the most extensive gastrointestinal resections.…”
mentioning
confidence: 99%
“…Several studies, most of which are case series and small comparative studies, have pointed out the feasibility and safety of minimal invasive surgery for ileocolic Crohn’s disease[2,3,4,5,6,7]. Despite the initial enthusiasm for the laparoscopic approach, only 2 RCTs comparing laparoscopic ileocolic resection (LIR) with conventional open ileocolic resection (CIR) have been conducted since the first reported LIR[ 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of different studies described a decreased duration of hospitalization of around 1-3 days. [6][7][8]11,13,16,[26][27][28] We analyzed our data to confirm if the length of stay was also shorter in the laparoscopic group.…”
Section: Length Of Staymentioning
confidence: 99%